An Elephant in the Desert - Sarveswaran, Vidya (The Trumpeter, 2015)
An Elephant in the Desert is a narrative that talks about the writer’s personal meeting with Terry Tempest Williams, the American writer from Utah. As a Fulbright scholar working on the writings of Williams, this personal meeting with Williams was one of the most defining moment of the writer’s life. The experiential narrative discusses issues ranging from the personal to the political and the sacred in Williams’s writings, the role of myth and legend and how they can redefine our ecological imagination. It also talks about staying deeply connected to the Universe at large how stories enact our life patterns, connect us to the physical world around us, and teach us stewardship.